Adverse drug reactions in medical inpatients. Issue 6 (June 1984) - Choonara, I A; Harris, F
Abstract : Fifteen of 268 children admitted to a general medical ward suffered a definite or probable adverse drug reaction to their treatment. In 6 of these children the reactions were preventable. Anticonvulsants were the most common cause of an adverse reaction.